Prevalência de pacientes em terapia renal substitutiva no Estado de São Paulo - Prado Louvison, Marilia Cristina; Marcondes Cecilio, Mônica Aparecida; Lopes Rodrigues Osiano, Vera Lucia; Lemes Cruvinel Portas, Silvany; Sesso, Ricardo (BEPA. Boletim Epidemiológico Paulista, 2011)